Explaining High Electoral Acceptance Amid International Integrity Concerns in Indonesia's 2024 Election - Azis, Mokhamad Abdul; Firdauz, Dimas Lazuardy; Wibisono, Rizky Bangun (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
One of the central issues in participatory democracy discourse concerns how the public perceives electoral integrity and accepts election outcomes. This study investigates the retrospective impact of regime performance and perceptions of electoral bureaucratic professionalism on trust and acceptance of the 2024 Indonesian presidential election results. Employing a quantitative-explanatory design with 250 respondents, data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that retrospective evaluations of government performance—particularly economic—positively and significantly influence both electoral trust and acceptance on result. Meanwhile, bureaucratic professionalism enhances electoral trust but does not directly affect acceptance. Theoretically, this study reinforces Easton’s political system model within an electoral framework and supports Norris’s electoral integrity model, suggesting that both regime performance and bureaucratic professionalism contribute to legitimizing election outcomes through the cultivation of systemic trust.